APLIKASI GEOGRAPHIC INFORMATION SYSTEM (GIS) DAN REPORTING JARINGAN FIBER OPTIC BERBASIS WEB DAN MOBILE APPLICATION - Tita Dwi Kesuma Saniswan; Yuli Kurnia Ningsih (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2019)
Geographic Information System (GIS) is an application that has many benefits and implementation, One of the GIS implementation is area mapping. implementation GIS for web based monitoring Fiber Optic networking system integrated with client in mobile application will be analyzed in this Thesis. The ability to send data and image real time also will be applied in this implementation. Parameters to be tested in the data transmission process between the system dashboard and mobile application is latency with a number of combinations of the number of clients. The result of the function test is that there is an increase in latency if the number of clients that access the dashboard system server is more. Latency is affected by signal strength on the client device and the location of data input on the client. The dashboard system is equipped with a Service Level Agreement (SLA) percentage calculation that is affected by the length of downtime or failure of the Fiber Optic network system. SLA calculations on the dashboard system are done automatically and the percentage generated is in accordance with manual mathematical calculations.